(Re)-fashioning the Techno-erotic Woman: Gender and Textuality in the Cybercultural - Handayani, Diah (Proceedings of International Conference on Da'wa and Communication, 2021)
This study examines the techno-journals and futuristic zines such as Boing Boing inscribe a kind of textual prologue for cyber-culture. They are valuable in themselves because they forge a much-needed connection between late print culture and the new cyberspatial network, formatting the matrix of this social space in ways that begin to define it. Wired magazine, for instance, participates in a cultural dialogue concerning issues of network privacy, governmental regulation, and censorship. Wired also sponsors HotWired, its online counterpart, where participants can exchange information, chat with live guests, and buy, sell, or trade computers and software products. Boing Boing, while differing from Wired in their hyperbolic presentation, share the techno-journal's fascination with "New Edge" culture, which includes, in addition to a hacker-like obsession with computers, technological phenomena such as raves, body alteration, smart drugs, and techno-spiritual movements. Because the communications revolution has brought about a phenomenological change in our perceptions of lived experience. These publications could be said to provide a type of public service by offering interfacing media that connect the user-friendly world of print with the phenomenon of cyberspatial networking. Yet, for all of their cutting-edge potential as links to the democratizing venues of cyberspace or as media for constructing alternative cybertextual practices, many of these techno-journals remain disturbingly vested in the politics of late capitalist culture. This includes heralding the new technologies in what amounts to an almost nostalgic longing for the ultimate "metanarrative"—pronouncing technological libertarianism and combining social consciousness with rampant consumerism.